The effectiveness of vacuum-assisted closure therapy in patients with infected venous leg ulcers - Tekin, Esra Erturk; Yesiltas, Mehmet Ali; Uysal, Ayhan; Haberal, Ismail (Clinics Cardive Publ Pty Ltd, 2022)
Aim: In this study, we aimed to investigate the effect of vacu-um-assisted closure therapy on venous stasis wound healing in patients with chronic venous leg ulcers. Methods: Vacuum-assisted closure therapy was applied on a total of 14 venous leg ulcers. All patients had post-thrombotic syndrome. Quantitative wound culture samples were obtained before the procedure and local wound assessments were performed. The primary outcome measures included wound healing as assessed by a local wound examination during each dressing change and the rate and velocity of ulcer reduc-tion. Wound healing was defined as the complete closure of the ulcer, while rapid wound healing was defined as a >= 30% reduction in the ulcer size by week four. Results: No surgical debridement or surgical corrective procedure was applied in any patient. The mean length of hospital stay was 32.3 days. The mean number of vacuum-assisted closure therapies for each case was 17.8 and the mean time to dressing change was 72.3 hours. Multidrug-resistant Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus were detected in three and four patients, respectively. Wound culture results became negative after a mean duration of vacuum-assisted closure therapy of 12.1 days. None of the patients needed antibiotic therapy until the procedure was completed. Compared to baseline, the mean ulcer reduction rates were 46.4% for the first six applications and 72.8% for the subsequent applications. Conclusion: Our study results suggest that vacuum-assisted closure therapy promotes rapid wound healing in patients with severe post-thrombotic syndrome with venous stasis leg ulcers, and reduces the need for antibiotics by reducing the biological burden.
Keywords: vacuum-assisted closure therapy; venous ulcer; post-thrombotic syndrome; wound infection; rapid wound healing